Uji Efektivitas Inokulum Fungi Mikoriza Arbuskula Terhadap Pertumbuhan Bibit Jati (Tectona Grandis Linn. F) - Kartika Megawati; Sri Wilarso Budi; Irdika Mansur (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Arbuscular mycorrhizal fungi is a phylum of Glomeromycota. Arbuscular mycorrhizal fungi (AMF) propagule are spores, mycor-rhizal fungal hyphae and infected root fragments. The aims of this research were to analyze the effectivity of root inoculum of AMF to enhance teak (Tectona grandis Linn F.) seedling growth. The research was used complete randomized design (CRD)-split plot design. The main plot was root inoculum of AMF, sub plot is a media sterilization and media is not sterilized. The results showed that root inoculum of AMF and media effectively improved teak growth, especially in height, diameter, and shoot dry weight. Root inoculum of AMF is able to be used as the source of inoculum for the growth teak seedling. Fresh inoculum was found to be better than root inoculum stored at room temperature and root inoculum stored at refrigerator temperature (5°C). Storage of root inocu-lum at room temperature and refrigerator temperature (5°C) for two weeks decreased the effectiveness of inoculum. Type of mixed inoculum and inoculum of Acaulospora sp. root resulted in better growth compared with G. clarum root inoculum.